The role of ancient and medieval Turkic written monuments in the study of modern Turkic languages - Hajiyeva, Aygul (International Journal of Psychosocial Rehabilitation, 2020)
The paper deals with the role of ancient and medieval Turkic written monuments in the study of modern Turkic languages. Being the sources of history, complex form of social life and institution, administrative and social hyerarchy, religion, and worldview of the Turkic peoples, they also give a possibility to trace the formation of the Turkic languages, their phonetic, lexical and grammatical systems. This study is based on descriptive, historical comparison, and comparative analysis methods. The methodology is a logical and philosophical theory applied to the historical development of language facts and addresses to the works of prominent turkologists in this aspect. For example, the history of agglutinative words system in Turkic languages, vowel prolongation and their types in Turkish phonetics, the problems arising in the learning of modern Turkish language vocabulary, the differentiation of syncretic affixes and adverbs. Type of Paper— Review